Hierarchically electrospraying a PLGA@chitosan sphere-in-sphere composite microsphere for multi-drug-controlled release. Issue 4 (14th April 2020) - Liu, Zhu; Ye, Weilong; Zheng, Jingchuan; Wang, Qindong; Ma, Guowu; Liu, Huiying; Wang, Xiumei
Abstract: Sequential administration and controlled release of different drugs are of vital importance for regulating cellular behaviors and tissue regeneration, which usually demands appropriate carriers like microspheres (MS) to control drugs releases. Electrospray has been proven an effective technique to prepare MS with uniform particle size and high drug-loading rate. In this study, we applied electrospray to simply and hierarchically fabricate sphere-in-sphere composite microspheres, with smaller poly(lactic-co-glycolic acid) MS (∼8–10 μm in diameter) embedded in a larger chitosan MS (∼250–300 μm in diameter). The scanning electron microscopy images revealed highly uniform MS that can be accurately controlled by adjusting the nozzle diameter or voltage. Two kinds of model drugs, bovine serum albumin and chlorhexidine acetate, were encapsulated in the microspheres. The fluorescence-labeled rhodamine-fluoresceine isothiocyanate (Rho-FITC) and ultraviolet (UV) spectrophotometry results suggested that loaded drugs got excellent distribution in microspheres, as well as sustained, slow release in vitro . In addition, far-UV circular dichroism and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) results indicated original secondary structure and molecular weight of drugs after electrospraying. Generally speaking, our research proposed a modified hierarchically electrospraying technique to prepare sphere-in-sphere composite MS with two different drugs loaded, which could be applied in sequential, multi-modality therapy.